Proceedings of IADC/SPE Drilling Conference 2006
DOI: 10.2523/97982-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Aphron Drilling Fluids

Abstract: TX 75083-3836, U.S.A., fax 1.972.952.9435. AbstractAphron drilling fluids are being used globally to drill through depleted reservoirs and other under-pressured zones. The primary features of these fluids are their unique low-shear rheology and aphrons (specially designed pressure-resistant microbubbles of air). However, how aphron drilling fluids work is not well understood, which limits acceptance of this technology, along with efforts to optimize the system's performance. Recently a study was undertaken und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The velocities of invading fluids tend to slow as a consequence of radial flow around the wellbore and the bridging action of the CGA bubbles. This causes their shear rates to decrease and viscosities to rise [73].…”
Section: Rheology Of the Prepared Gca-based Fluidsmentioning
confidence: 99%
“…The velocities of invading fluids tend to slow as a consequence of radial flow around the wellbore and the bridging action of the CGA bubbles. This causes their shear rates to decrease and viscosities to rise [73].…”
Section: Rheology Of the Prepared Gca-based Fluidsmentioning
confidence: 99%
“…The potential of aphrons as components of drilling fluids rests in their ability to form a solid free, tough, and elastic internal bridge in pore networks or fractures to minimize deep invasion by means of air microbubbles (Belkin et al, 2005;Growcock et al, 2003). This microenvironment seal readily cleans up with reservoir flow-back as production is initiated, thereby reducing cost associated with stimulation processes (Growcock et al, 2006;Ivan et al, 2002). The use of CGAs as a drilling/completion fluid also presents several advantages.…”
Section: Introductionmentioning
confidence: 96%
“…The use of CGAs as a drilling/completion fluid also presents several advantages. The high carrying capacity, the minimum amount of fluid placed in the formation, and the excellent fluid recovery after treatment are some of the advantages that CGA based fluids present when used during operations (Brookey, 1998;Growcock et al, 2006). The major implementation of rheological parameters for evaluating drilling fluid behavior are in solving problems of hydraulic calculations, suspension of cuttings and hole cleaning (Arabloo et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Microfoam has a drainage half-life up to 24 hours, which shows good dynamic stability and coagulation stability [4] . Microfoam has strong toughness and deformability and it can match different sizes of pore channels, thus an effective plugging can be obtained [5] . It has been observed that microfoam fluid showed more stable frontal displacement and lower injection pressure as compared to polymer solutions [6] .…”
Section: Introductionmentioning
confidence: 99%